An analysis of the environment and competitive dynamics of management research - Howard Thomas; Alex Wilson (2009)
Purpose: This paper examines some of the controversies facing business schools in their future evolution and pays particular attention to their competitive positioning as centres of management research. Design/methodology/approach: The paper combines and builds on current literature to provide an analytic overview of the environment and competitive challenges to management research in business schools. Findings: The paper assesses the impacts of a globalised environment and ever-changing competitive dynamics, for example in terms of the supply of high-quality faculty, on the activity of management research in business schools. It points out that research impacts must be judged not only in terms of theoretical development but also managerial and policy impact. However, managerial impact is difficult to measure and the ‘voice of practice’ must be carefully identified. Originality/value: The paper identifies the current challenges for undertaking innovative research in business schools in light of their competitive environment. Three interrelated conjectures focussing particularly on managerial impact are raised which identify problems and limitations of current debates on management research in business schools.